2020
DOI: 10.1093/jas/skaa259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a microencapsulated formula of organic acids and essential oils on nutrient absorption, immunity, gut barrier function, and abundance of enterotoxigenic Escherichia coli F4 in weaned piglets challenged with E. coli F4

Abstract: The objective was to study the effects of microencapsulated organic acids (OA) and essential oils (EO) on growth performance, immune system, gut barrier function, nutrient digestion and absorption, and abundance of enterotoxigenic Escherichia coli F4 (ETEC F4) in the weaned piglets challenged with ETEC F4. Twenty-four ETEC F4 susceptible weaned piglets were randomly distributed to four treatments including (1) sham-challenged control (SSC; piglets fed a control diet and challenged with phosphate-buffered salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 93 publications
4
44
0
Order By: Relevance
“…The previous study has demonstrated that dietary supplemented with mixed organic acid could improve performance ( 14 ), immune function ( 5 , 15 ), intestinal morphology as well as intestinal microbiota ( 10 , 16 ). Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry ( 4 , 17 ), especially in weaning pigs ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has demonstrated that dietary supplemented with mixed organic acid could improve performance ( 14 ), immune function ( 5 , 15 ), intestinal morphology as well as intestinal microbiota ( 10 , 16 ). Also, numerous scholars have illustrated the mechanism of MOA and summarized the benefits of MOA in livestock and poultry ( 4 , 17 ), especially in weaning pigs ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…After 3-day adaptation, the piglets were assigned randomly, on the basis of body weight (BW) and litter origin, to 8 groups: (8 piglets/group): 1) control group -piglets fed the basal diet and treated with phosphate buffered saline (PBS, pH = 7.4); 2) CT group -piglets fed the basal diet supplemented with 40 mg/kg BW of colistin (CT; Zhongnong Pharmaceutical, Xinxiang, China); 3) LL grouppiglets fed the basal diet supplemented with 1 × 10 7 LB1/pig/day (relative low concentration of LB1, LL); 4) HL group -piglets fed the basal diet supplemented with 1×10 8 CFU/pig/day LB1 (relative high concentration of LB1, HL); 5) ETEC group: piglets fed the basal diet, and challenged with 1 × 10 10 CFU/pig ETEC; 6) CT + ETEC group -piglets fed the basal diet supplemented with 4 mg/kg BW of CT, and challenged with 1 × 10 10 CFU/pig ETEC; 7) LL + ETEC group -piglets fed the basal diet supplemented with 1 × 10 7 CFU/pig/day LB1, and challenged with 1 × 10 10 CFU/pig ETEC; 8) HL + ETEC group -piglets fed the basal diet supplemented with 1 × 10 8 CFU/pig/day LB1, and challenged with 1 × 10 10 CFU/pig ETEC. Before the animal trial, faeces from each piglet was tested for ETEC by PCR analysis using primers specific to faeG (Zhu et al, 2011) and the method described by Choi et al (2020). No ETEC was detected in the faecal samples.…”
Section: Animals and Trial Designmentioning
confidence: 99%
“…In the present study, ETEC F4 bacteria, isolated from feces of piglets infected with postweaning diarrhea in the Veterinary Diagnostic Services Laboratory from the Government of Manitoba in Canada, was used to establish the model of harmful bacteria invasion in vitro. A previous study from this laboratory, showed that this strain of ETEC F4 can affect the nutrient absorption, immunity and gut barrier function in weaned piglets [39]. It was hypothesized that B. licheniformis PF9 isolated from feces of piglets in this study may be involved in attenuating/ ameliorating ETEC-induced changes in mucosal barrier function and the in ammatory responses of intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 83%